Distribution coefficients K of cobalt ions in soil samples of Anarak near-surface radioactive waste repository studied by batch and three different column methods - Esmaeiliboosjin, Maliheh; Aminisisakht, Marzieh; Poursharifiravari, Mohadeseh; Dara, Mojtaba; Samadfam, Mohammad (Nuclear engineering and technology, 2024)
The selection of appropriate transport parameters of radionuclides is of utmost importance in the safety assessment of radioactive waste disposal sites. Both batch and column methods are widely performed to determine the transport parameters of radionuclides through soil layers. In this paper, the distribution coefficients Kd of Co ions in sandy mixtures containing soil samples taken from Anarak near-surface repository (Iran) were determined by batch and 3 different column methods namely, breakthrough curve, thin-section, and gamma spectroscopy methods. The distribution coefficients Kd of the mixture was obtained as 160 L kg 1 for the batch method, 23 L kg 1, 19 L kg 1, and 18 L kg 1 for the breakthrough curve, the thin-section, and the gamma spectroscopy methods, respectively. These results emphasize proper selection of transport data for using in the safety assessment programs KCI Citation Count: 0